2008
DOI: 10.1115/1.2771243
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Flexibility Influences on Premixed Combustor Blowout, Flashback, Autoignition, and Stability

Abstract: This paper addresses the impact of fuel composition on the operability of lean premixed gas turbine combustors. This is an issue of current importance due to variability in the composition of natural gas fuel supplies and interest in the use of syngas fuels. This paper reviews available results and current understanding of the effects of fuel composition on combustor blowout, flashback, dynamic stability, and autoignition. It summarizes the underlying processes that must be considered when evaluating how a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(130 citation statements)
references
References 45 publications
1
129
0
Order By: Relevance
“…Under a high ambient temperature of 1000 K, Figure 4 demonstrated that combustion recession appears as a connected, backward-traveling wave possibly driven by flame propagation processes. But, the speed of combustion recession for this condition is approximately 200 m/s and is much faster than gas-turbine studies that measured flashback speeds on the order of typical turbulent flame speeds [30,31]. Furthermore, as the ambient temperature was reduced to 900 K in Figure 4, combustion recession appeared as isolated ignition sites that merged with time, which is inconsistent with the concept of a propagating flame sheet.…”
Section: Description Of Combustion Recession Based On Measurements Anmentioning
confidence: 41%
“…Under a high ambient temperature of 1000 K, Figure 4 demonstrated that combustion recession appears as a connected, backward-traveling wave possibly driven by flame propagation processes. But, the speed of combustion recession for this condition is approximately 200 m/s and is much faster than gas-turbine studies that measured flashback speeds on the order of typical turbulent flame speeds [30,31]. Furthermore, as the ambient temperature was reduced to 900 K in Figure 4, combustion recession appeared as isolated ignition sites that merged with time, which is inconsistent with the concept of a propagating flame sheet.…”
Section: Description Of Combustion Recession Based On Measurements Anmentioning
confidence: 41%
“…Additionally, although some attentions have been devoted on the effect of fuel type in combustion instability [16][17][18] and combustion noise [19], no work has been focused on the transmitted noise rising from a burned gases of a traditional or novel composite fuel in an exit combustor nozzle; as the whole above studies applied hot air as the working fluid. These conditions, however, are really found in an exit nozzle of a combustor in industrial or aero-engine gas turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Most operating conditions have been shown to influence the thermo-acoustic stability of the combustor. Equivalence ratio as well as fuel composition, mixture preheat temperature, and other flow properties like swirl and Reynolds numbers' effect on dynamic instabilities have been investigated [1][2][3][4][5][6][7][8]. Because of its critical importance, thermoacoustic instabilities arising in premixed combustion have been extensively studied for decades and are still an active area of research.…”
Section: Introductionmentioning
confidence: 99%